The effect of adsorbent additive on clay based adsorbent to the removal of a single dye system - Mohd. Khairi, Kamarudin (2010)
One of the powerful treatment processes for the removal of dyes from water at low cost is adsorption. This research is studied to identify which one is the best additive used for removal of dyes solution from wastewater. This dyes containing wastewater discharge in stream and river and will cause the major sources of water pollution. The main objective of this research is to study the effect of adsorbent additive on clay base to the removal of a single dye system. Scope of this research are to study the effect of single dye by adding the different ratio of additive with clay and to study the influenced of pH towards dye removal performance. For each parameter studied, clay will keep as a constant parameter and three additives are used to increase the efficiency of dye removal from wastewater which is zeolite, chitosan and powdered activated carbon. Clay and additives are adsorbent but in this research studied for the one of the additive will adsorb more dyes if mixed with the clay. For the pH parameter, stock solution of Methylene Blue prepared and mass of the clay and the additive set to constant. Stock solution then divided into 250ml beaker. The initial and final concentration determined by using the Uv-vis spectrophotometer. Standard curve prepared for this equipment to get the value of the concentration of each sample. The range of pH used between 1 to 14. The results showed that all of three additives are effective at pH 14 for alkali solution. For acidic solution, powdered activated carbon and chitosan effective at pH 3 but zeolite effective at pH 1. For ratio study, the experiments were conducted by adding different amount of additive into a constant amount of clay. From the data collected shows that the powdered activated carbon is the most effective additive compared to chitosan and zeolite which have highest percentage of dye removal at 96.86% for alkali dye solution. This occurs at the weight of 1g clay added with 1.5g powdered activated carbon. However, 90% of dye is removed for acidic solution when ratio of clay and additive are similar. As a conclusion, powdered activated carbon is the most effective additive used for removal of dye in solution compared than chitosan and zeolite. Further research should be studied to look forward the cheaper additives to substitute the powdered activated carbon but the performance of adsorption will not effect.